Chapter "Experience that Generates Experience": The Influence of the Comedy in three South African Writings - Medugno, Marco (Studi e saggi, 2021)
This article aims to explore the intertextual relationships between Dante's Divine Comedy and three pieces of creative writing: Chariklia Martalas' "A Mad Flight into Inferno Once Again", Thalén Rogers' "The Loadstone" and Helena van Urk's "The Storm". By employing a comparative analysis, I argue that, even though decontextualised, the Comedy still represents a fruitful aesthetic source for representing particularly war-torn and violent contexts such as South Africa during apartheid and colonialism. I explore how the authors, through intertextual references and parodic rewriting, both re-configure the poem and challenge some of the Comedy's moral assumptions and the idea of (divine) justice. I aim to show how Dantean Hell, far from being an otherworldly realm, is in fact transfigured and adapted to effectively represent (and make sense of) a historical context. In other words, through an intertextual analysis, this analysis tries to understand why and how the Comedy resonates with the South African socio-political (and literary) context.